2009
DOI: 10.1016/j.neuron.2009.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Dscam Mediates Remodeling of Glutamate Receptors in Aplysia during De Novo and Learning-Related Synapse Formation

Abstract: Transsynaptic interactions between neurons are essential during both developmental and learning-related synaptic growth. We have used Aplysia neuronal cultures to examine the contribution of transsynaptic signals in both types of synapse formation. We find that during de novo synaptogenesis, specific presynaptic innervation is required for the clustering of postsynaptic AMPA-like but not NMDA-like receptors. We further find that the cell adhesion molecule Dscam is involved in these transsynaptic interactions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
85
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 35 publications
1
85
0
Order By: Relevance
“…Scaling in those cases has additional similarities to intermediate-and long-term facilitation: Both types of plasticity can involve postsynaptic Ca 2+ (8,23,33), protein synthesis (8,23,34), AMPA receptor insertion (7,8,16,33), and modulation of the presynaptic probability of release (10)(11)(12)15). However, scaling has an opposite sign of action compared with facilitation (during scaling, spontaneous release acts to decrease protein synthesis and synaptic strength).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scaling in those cases has additional similarities to intermediate-and long-term facilitation: Both types of plasticity can involve postsynaptic Ca 2+ (8,23,33), protein synthesis (8,23,34), AMPA receptor insertion (7,8,16,33), and modulation of the presynaptic probability of release (10)(11)(12)15). However, scaling has an opposite sign of action compared with facilitation (during scaling, spontaneous release acts to decrease protein synthesis and synaptic strength).…”
Section: Discussionmentioning
confidence: 99%
“…Long-term plasticity can differ from short-term in recruiting the growth of new synaptic connections, a process that requires the participation of both the presynaptic and postsynaptic components of the synapse (15)(16)(17)(18)(19)(20)(21). Because short-term plasticity often involves only one component of the synapse (22)(23)(24), the question arises: How does information about synaptic plasticity spread from its site of origin to recruit the other component of the synapse?…”
mentioning
confidence: 99%
“…Those mechanisms could serve as early steps in a program leading to synaptic growth during long-term facilitation, which also involves both pre-and postsynaptic mechanisms coordinated by transynaptic signaling (Trudeau and Castellucci 1995;Kandel 2001;Sherff and Carew 2004;Cai et al 2008;Li et al 2009;Wang et al 2009). That idea in turn raises a number of new questions about the stages and their interrelations.…”
Section: Mechanisms Of Intermediate-term Facilitationmentioning
confidence: 99%
“…On the one hand, under some circumstances short-and long-term plasticity can be produced independently, suggesting that they may be induced in parallel (Emptage and Carew 1993). On the other hand, in both Aplysia and hippocampus an intermediate-term stage of plasticity has been identified that usually involves protein but not RNA synthesis and structural alterations but not synaptic growth, and therefore might form a bridge between short-and long-term plasticity (Ghirardi et al 1995;Winder et al 1998;Sutton and Carew 2000;Sutton et al 2001;Kim et al 2003;Li et al 2005Li et al , 2009Villareal et al 2007). That idea in turn suggests that aspects of the different stages of plasticity may be induced in series, similar to the states in artificial "cascade" models of memory storage (Fusi et al 2005).…”
mentioning
confidence: 99%
“…synaptic plasticity | metabotropic glutamate receptor | octopamine | latrotoxin | botulinum toxin W hereas short-term (minutes) facilitation in Aplysia involves covalent modifications restricted to the presynaptic neuron, long-term (days) facilitation is accompanied by the growth of new synapses, which involves coordinated pre-and postsynaptic structural changes (1)(2)(3)(4). Those findings raise two questions that are applicable to other forms of plasticity that can involve synaptic growth, such as the late phase of long-term potentiation (LTP) in the hippocampus (5)(6)(7)(8)(9) and other brain areas: (i) What signaling mechanisms coordinate the pre-and postsynaptic changes, and (ii) when is that signaling first engaged?…”
mentioning
confidence: 99%